New forms of work organisation 1 : Denmark, Norway and Sweden, France, Federal Republic of Germany, United Kingdom, United States - International Labour Office (Geneva : International Labour Office, 1979)
This volume is the latest development in a recent series of activities launched by the International Labour Office with regard to improvements in the organization of work. In this field the Office has been activity assisted under sub-contract by the International Institute for Labour Studies. This work has laid the foundation for future ILO activities concerning work organization and job content. These activities include a closer study of specific problems of work organization as it affects different sectors of the economy, and the preparation of material to encourage the adoption and effective use of better forms of work organization.
Includes bibliographical references.
rpm 05/12/2017
Loans
Keywords: Working class; Industrial organization; Work design